2014
DOI: 10.1136/jnnp-2014-309243
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of interferon β versus glatiramer acetate for relapsing-remitting multiple sclerosis

Abstract: Interferon β (INFβ) and glatiramer acetate (GA) are widely used in patients with relapsing-remitting multiple sclerosis (RRMS). However, it is still unclear whether they have different efficacy. We performed a systematic search of head-to-head trials for gaining objective reliable data to compare the two drugs, using the Cochrane Collaboration methodology. We identified five randomised-controlled trials (RCTs) (2858 participants) comparing directly INFβ versus GA in RRMS. All studies were at high risk for attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…A systematic review (five randomised controlled trials, 2858 participants) comparing interferon beta preparations and glatiramer acetate found a similar effect on relapses and disability progression, although secondary MRI endpoints favoured interferon beta 33. In separate phase III randomised controlled trials, interferon beta had similar efficacy to teriflunomide, and was less effective than fingolimod, alemtuzumab, and ocrelizumab 18192021222326…”
Section: How Well Do They Work?mentioning
confidence: 99%
“…A systematic review (five randomised controlled trials, 2858 participants) comparing interferon beta preparations and glatiramer acetate found a similar effect on relapses and disability progression, although secondary MRI endpoints favoured interferon beta 33. In separate phase III randomised controlled trials, interferon beta had similar efficacy to teriflunomide, and was less effective than fingolimod, alemtuzumab, and ocrelizumab 18192021222326…”
Section: How Well Do They Work?mentioning
confidence: 99%
“…A systematic review summarising data from five randomised studies comparing IFN-β with GA in patients with RRMS confirmed a similar efficacy after 2 years of treatment [62].…”
Section: Once-daily Formulation In Relapsing-remitting Multiple Sclermentioning
confidence: 99%
“…2 When a prescribed DMD is judged ineffective, it should be either substituted with another first-line drug or switched with a second-line (fingolimod or natalizumab for anti-JC virus antibody-negative patients) or third-line (natalizumab for anti-JC virus antibody-positive patients) drug. 2,4 While switching between first-line drug therapies, a Cochrane Collaboration methodology-based study reported reliable data comparing IFNb and GA, and concluded the two therapies do not seem to differ in terms of clinical efficacy and safety, although IFN was found to limit the increase of MRI lesion burden more than GA. 35 With similar safety and efficacy in the prevention of disease activity, clinicians can select a therapy preferable for their patient based on MRI measures and tolerability differences. 2,4 While switching between first-line drug therapies, a Cochrane Collaboration methodology-based study reported reliable data comparing IFNb and GA, and concluded the two therapies do not seem to differ in terms of clinical efficacy and safety, although IFN was found to limit the increase of MRI lesion burden more than GA. 35 With similar safety and efficacy in the prevention of disease activity, clinicians can select a therapy preferable for their patient based on MRI measures and tolerability differences.…”
Section: Positioning Of Each Dmd and Treatment Strategymentioning
confidence: 99%
“…2,4 This stepwise use of DMD, wherein the safety risk increases with stronger potency for suppression of MS disease activity, is termed as escalation therapy. 35 Highly active disease in MS patients is defined as more than two clinical relapses within the previous 12 months, two separate MRI scans showing more than a few Gd-enhancing lesions and/or new or enlarging T2 lesions, and rapid progression of the Expanded Disability Status Scale score. 35 Highly active disease in MS patients is defined as more than two clinical relapses within the previous 12 months, two separate MRI scans showing more than a few Gd-enhancing lesions and/or new or enlarging T2 lesions, and rapid progression of the Expanded Disability Status Scale score.…”
Section: Positioning Of Each Dmd and Treatment Strategymentioning
confidence: 99%